The Concept of I'jaz Al-Qur'an and Its Various Manifestations: A Study of I‘jaz Lughawi, Tasyri‘i, ‘Ilmi, and Ghaibi - Sabili, Sabili; Nasrullah Bin Sapa; Muhammad Amin Sahib (Penerbit Hellow Pustaka, 2025)
This research aims to comprehensively examine the concept of I'jaz Al-Qur'an (the Miraculousness of the Qur'an) by analyzing its definition, various forms, and primary content, to affirm its status as the sole and eternal proof of the truth of the message of Prophet Muhammad ﷺ. The method employed is descriptive qualitative, utilizing a library research approach, which involves content analysis of classical Ulumul Qur'an works and contemporary literature. The findings indicate that I'jaz is a multidimensional phenomenon that renders all human attempts to imitate the Qur'an incapable (a'jaza). The forms of I'jaz are classified into three main aspects: I'jaz al-Lughawi (linguistic), as the foundation of its miraculousness, which lies in its unparalleled nazhm (composition) and balaghah (eloquence); I'jaz at-Tasyri'i (legislative and moral), which guarantees the perfection and relevance of the Qur'an's universal and eternal laws; and I'jaz al-'Ilmi (scientific), which serves as a modern confirmation of its scientific allusions. It is concluded that the content of the Qur'an—comprising Aqidah (creed), Ibadah (worship), Muamalah (social transactions), and Akhlak (ethics)—is integrated, and its coherence is part of the miraculousness itself. Overall, I'jaz Al-Qur'an is an integration of the beauty of form (language), the perfection of function (law), and the truth of content (scientific), making it a miracle that continues to speak to the mind and heart in every era